Factors affecting variability in feedlot steer profits - Langemeier, Michael R.; Mintert, J.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study examined the relative importance of price and animal performance factors on cattle finishing profitability. Using data from a single feedlot, sale prices, feeder prices, and corn prices explained 90 to 95% of the variation in steer profits. About 50% of the variability was explained by fed cattle prices alone. Because sale, feeder, and corn prices have a large impact on profits per head, cattle feeders should attempt to manage the risks associated with these three factors.
Keywords: Beef; Cattle finishing profitability; Sale prices; Feeder cattle prices